2005
DOI: 10.1212/01.wnl.0000168901.98616.1c
|View full text |Cite
|
Sign up to set email alerts
|

Impaired spatial coding within objects but not between objects in prosopagnosia

Abstract: Impaired perception of spatial relations in prosopagnosia is selective to the spatial structure within individual objects and spares the perception of spatial location of objects. It is not specific to faces. It reveals a process involved in analyzing object structure, consistent with the patients' deficits in recognizing facial identity, and illustrates a different type of "visuospatial" defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(87 citation statements)
references
References 21 publications
3
78
6
Order By: Relevance
“…Patients with prosopagnosia are more impaired on within-object spatial judgments while those with Balint syndrome are more impaired on between-object spatial tasks [34,35]. Most of the visuospatial tasks used to assess aMCI have focused on between-object spatial functions [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with prosopagnosia are more impaired on within-object spatial judgments while those with Balint syndrome are more impaired on between-object spatial tasks [34,35]. Most of the visuospatial tasks used to assess aMCI have focused on between-object spatial functions [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Representative MRI scans are shown in Figure 1, and anatomic templates in Figure 2. More detailed case information on most of these subjects can be found in previous reports using the same subject identification numbers (Barton et al, 2004a,Barton et al, 2004b,Barton and Cherkasova, 2005.…”
Section: Methodsmentioning
confidence: 99%
“…The task was to indicate which apex was farther away. In our prior report, we showed that prosopagnosic subjects with or without hemifield defects (including subjects 005 and 010) could make accurate judgments of similar spatial distances between stimuli under time-limited viewing conditions (8). The six stimuli were designed to approximate a progression from between-object to within-object spatial coding (Fig.…”
Section: Testingmentioning
confidence: 99%
“…A study of a subject with Bálint syndrome suggested that betweenobject representations may be selectively impaired in this condition (7). In that regard, we have recently provided evidence from a series of patients with prosopagnosia, the inability to recognize familiar faces, that their perception of the fine metrics of within-object and within-face spatial relations is impaired, but their between-object spatial judgments are normal (8).…”
mentioning
confidence: 90%